The The Role of Effective Business Communication in Enhancing Employee Performance: A study at RSUD Bumiayu - Muhammad Ali Ghozi; Dian Purnomo Jati; Eman Purnomo Sutrisna (Faculty of Economics and Business, Jenderal Soedirman University, 2026)
This study aims to analyze the effect of organizational communication on employee performance at RSUD Bumiayu. Organizational communication in this research is measured through three dimensions: upward communication, downward communication, and horizontal communication. The method employed is a quantitative approach using explanatory research. Data were collected through the distribution of questionnaires using a 5-point Likert scale to 44 respondents who are employees of RSUD Bumiayu. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 22.The results indicate that all three forms of organizational communication have a positive and significant influence on employee performance. The coefficient of determination test (R²) shows that 53.5% of the variation in employee performance can be explained by the three communication variables, while the remaining 46.5% is influenced by other factors beyond this study. Classical assumption tests, including normality, multicollinearity, and heteroskedasticity, also confirm that the model meets the required statistical criteria, thus validating the regression model.This research concludes that effective organizational communication, both vertical (upward and downward) and horizontal, plays a crucial role in enhancing employee performance. The findings offer practical implications for the management of RSUD Bumiayu to strengthen open, participative, and two-way communication patterns in order to support performance improvement and the achievement of organizational goals.